1991
DOI: 10.1111/j.0022-3646.1991.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

CELL SURVIVAL CHARACTERISTICS AND MOLECULAR RESPONSES OF ANTARCTIC PHYTOPLANKTON TO ULTRAVIOLET‐B RADIATION1

Abstract: Twelve species of Antarctic diatoms were studied to assess UV sensitivity in relation to cellular and molecular aspects of DNA damage and repair. Responses of cell survival, induction of DNA damage, and DNA repair capacity were determined. There was a wide range of interspecific UV‐sensitivity among diatoms. D37 values (average fluence to kill one cell) ranged from 681 J · m−2 (most sensitive) to 25,338 J · m−2 (most resistant). Molecular analysis (by radioimmunoassay) of UV‐induced DNA damage [induction of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
338
6
16

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(386 citation statements)
references
References 53 publications
26
338
6
16
Order By: Relevance
“…However, the relationship between size and sensitivity is not straightforward. For example, Karentz et al (1991), studying 12 species of diatoms, concluded that smaller cells sustained greater amounts of damage per unit of DNA. On the other hand, Helbling et al (2001) showed that small flagellates are strongly inhibited by UV-R, but are able to acquire resistance to UV-R by photoadaptive processes.…”
Section: Higher Sensitivity Of Bacteria To Uv-bmentioning
confidence: 99%
“…However, the relationship between size and sensitivity is not straightforward. For example, Karentz et al (1991), studying 12 species of diatoms, concluded that smaller cells sustained greater amounts of damage per unit of DNA. On the other hand, Helbling et al (2001) showed that small flagellates are strongly inhibited by UV-R, but are able to acquire resistance to UV-R by photoadaptive processes.…”
Section: Higher Sensitivity Of Bacteria To Uv-bmentioning
confidence: 99%
“…Carotenoids also act in a photoprotective function against high irradiance (Demers et al 1991). Organisms have varying abilities to reverse the effects of UV radiation (Karentz et al 1991;Lesser et al 1996). Repair may be ongoing , may mostly occur after UV exposure (A. T. Banaszak et al unpubl.…”
Section: Datementioning
confidence: 99%
“…It has not been easy to develop fully satisfactory estimates of the effects of UVR on primary production, partly because UVR belongs to a continuous solar radiation spectrum that acts both beneficially and detrimentally on photosynthesizing organisms. Solar radiation drives the photosynthetic conversion of inorganic carbon to organic substrates, yet excessive visible light, as well as UVR, can inhibit photosynthesis (Cullen and Lesser 1991;Villafañe et al 1995), damage intracellular components such as DNA (Karentz et al 1991;Prézelin et al 1994), and inactivate certain key photosynthetic proteins (Greenberg et al 1989;Wilson et al 1995). Another major complication in assessing the effects of UVR on plankton is the natural variability in exposure regime that is associated with vertical mixing processes (Smith and Cullen 1995).…”
mentioning
confidence: 99%
“…Phytoplankton have evolved a variety of mechanisms to prevent or counteract the damage from UVR and excessive 1 Corresponding author (vphiriar@sciborg.uwaterloo.ca). light, such as DNA photoreactivation, the synthesis of photoprotective pigments, and dark repair processes (Karentz 1999;Roy 2000). Although the timescales of photoinhibition vary on the order of minutes to hours, some photoprotection measures occur within seconds or minutes (e.g., energy dissipation via fluorescence, state transitions, or nonradiative decay), and others occur on the order of hours to days (e.g., synthesis of protective pigments, or chemical quenchers; Ferris and Christian 1991;Villafañe et al 1995).…”
mentioning
confidence: 99%